The star cluster frequency throughout the Large Magellanic Cloud - Piatti, Andres Eduardo (2014)
We address the issue of the variation in star cluster frequency (CF) in the Large Magellanic Cloud (LMC) in terms of cluster spatial distribution. We adopt the LMC regions traced by Harris & Zaritsky and use an updated version of the cluster data base compiled by Baumgardt et al.. The CFs were produced by taking into account an appropriate selection of age bins. Since the uncertainty in a cluster's age can be large compared with the size of the age bins, we account for the fact that a cluster could actually reside in one of a few adjacent age bins. We confirm that there exist some variations of the LMC CFs in terms of spatial distributions, although some caveats should be pointed out. 30 Doradus turns out to be the region with the highest relative frequency of the youngest clusters, while the log(t) = 9–9.5 (1–3 Gyr) age range is characterized by cluster formation at a higher rate in the inner regions than in the outer ones. We compared the observed CFs with theoretical ones, based on the star formation histories of the field stars in each region of the LMC, and found that the former predicted more or fewer clusters than observed, depending on the field and age range considered.